E2‐mediated EMT by activation of β‐catenin/Snail signalling during the development of ovarian endometriosis. Issue 12 (27th September 2019) - Xiong, Wenqian; Zhang, Ling; Liu, Hengwei; Li, Na; Du, Yu; He, Haitang; Zhang, Zhibing; Liu, Yi
Abstract: Endometriosis is an oestrogen‐dependent disease, and epithelial‐mesenchymal transition (EMT) is involved in the process of endometriosis. Whether oestrogen could induce EMT in endometriosis remains largely unknown. Here, we reported that up‐regulated expression of EMT markers in ovarian chocolate cyst is accompanied by high expression 17β‐hydroxysteroid dehydrogenase 1 (17β‐HSD1), and exposure of primary human endometrial epithelial cells to oestradiol conditions could promote EMT occurrence and activate both β‐catenin and Snail signalling. Furthermore, we found nuclear β‐catenin and Snail expression was closely linked in ovarian endometriosis, and β‐catenin knockdown abrogated oestrogen‐induced Snail mediated EMT in vitro. This is due to that β‐catenin/ TCF‐3 could bind to Snail promoter and activate its transcription. These results suggested that β‐catenin signalling functions as the Snail activator and plays a critical role in oestradiol‐induced EMT in endometriosis.